Design of Buried Reinforced Concrete Pipes with Analytical and Numerical Methods - Demirci, Onur; Kilic, Havvanur; Yazici, Gokhan (TURKISH CHAMBER CIVIL ENGINEERS, 2022)
Buried reinforced concrete pipes are critical components of urban infrastructure. Their design can be conducted using empirical or numerical methods, which consider the properties of the pipes, backfill surrounding the pipe, bedding conditions and loads acting on the pipes. In this paper, a parametric study taking into account different backfill materials, burial depths, and pipe diameters was utilized to investigate the differences in design calculations obtained from widely accepted empirical and numerical analysis methods. Results indicate that required reinforcement areas calculated using numerical analyses are smaller than those obtained from traditional design methods due to realistic consideration of soil-pipe interaction.
Keywords: Buried concrete pipe design; indirect method; direct method; soil-structure interaction; numerical analysis; Engineering